2007
DOI: 10.1128/iai.01329-06
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-23 (IL-23)-IL-17 Cytokine Axis in Murine Pneumocystis carinii Infection

Abstract: Host defense mechanisms against Pneumocystis carinii are not fully understood. Previous work in the murine model has shown that host defense against infection is critically dependent upon host CD4 ؉ T cells. The recently described Th17 immune response is predominantly a function of effector CD4 ؉ T cells stimulated by interleukin-23 (IL-23), but whether these cells are required for defense against P. carinii infection is unknown. We tested the hypothesis that P. carinii stimulates the early release of IL-23, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
163
2
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(181 citation statements)
references
References 43 publications
(50 reference statements)
12
163
2
2
Order By: Relevance
“…Pulmonary Pneumocystis carinii infection also induced IL-23 and IL-17, and protection against the fungi depended on both IL-23 and IL-17 (32). Since IL-23/IL-17 axis participated in protective acquired immunity against the all three fungal infections, Th17 would be important in protective response against fungal infections.…”
Section: Role Of Il-17 In Immune Response Against Fungal Pathogensmentioning
confidence: 99%
“…Pulmonary Pneumocystis carinii infection also induced IL-23 and IL-17, and protection against the fungi depended on both IL-23 and IL-17 (32). Since IL-23/IL-17 axis participated in protective acquired immunity against the all three fungal infections, Th17 would be important in protective response against fungal infections.…”
Section: Role Of Il-17 In Immune Response Against Fungal Pathogensmentioning
confidence: 99%
“…65 Th17 cells also have an increasingly recognized role in the adaptive immune response to a variety of fungal pathogens. 66,67 Chamilos et al found that exposure of the b-glucan component of the cell wall of a mutant strain of H. capsulatum decreased its pathogenicity and stimulated an increased production of IL-23 by DCs and a resultant Th17 antifungal response. 68 This was found using a mutant strain of H. capsulatum that is unable to generate a-glucan, thereby exposing b-glucan to DCs.…”
Section: Dendritic Cells In the Immune Responsementioning
confidence: 99%
“…However, comparisons of indeterm inate results are difficult to make due to the lack of a validated cutoff for an indeterminate IP-10 response (see below). The immunological mechanisms underlying these suggested differences between IFN-g and IP-10 in HIV-infected patients are as yet unknown, but are probably due to a combination of both the higher magnitude of response and the broader induction profile of IP-10 compared with IFN-g [37][38][39][40][41][42][43][44][45][46]. Sutherland and colleagues recently demonstrated that coincident with the loss of total CD4 count, the TB antigen-specific immune response changed from a polyfunctional CD4 response to a monofunctional IFN-g or TNF-a CD8 T-cell response [74].…”
Section: Reviewmentioning
confidence: 99%
“…IP-10 secretion appears to be driven by multiple signals, mainly T-cell-derived IFN-g, but also IL-2, IFN-a, IFN-b, IL-27, IL-17, IL-23, and autocrine APC-derived TNF-a and IL-1b. TNF-a is a weak IP-10 inducer per se, but a potent synergistic inducer when acting with the interferons [37][38][39][40][41][42][43][44][45][46]. Because of the many different pathways that can lead to IP-10 secretion, IP-10 can be considered a downstream marker to typical readout markers in CMI assays, such as IL-2 and IFN-g [47,48].…”
Section: The Immunological Basis Of Ip-10 As a Readout Marker In CMI mentioning
confidence: 99%